Labor Markets in Asia Issues and Perspectives - Felipe, Jesus; Hasan, Rana (Palgrave Macmillan UK, 2006)
This volume argues that while labour market reforms may be necessary in some specific cases, by no means are labour market policies the main explanation for the widespread increase in unemployment and underemployment across Asia and country specific studies undermine the case for across-the-board labour market reforms